2007
DOI: 10.1111/j.1529-8817.2007.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

DESCRIPTION OF A NEW GENUS OF PFIESTERIA‐LIKE DINOFLAGELLATE, LUCIELLA GEN. NOV. (DINOPHYCEAE), INCLUDING TWO NEW SPECIES: LUCIELLA MASANENSIS SP. NOV. AND LUCIELLA ATLANTIS SP. NOV.1

Abstract: A new genus of Pfiesteria-like heterotrophic dinoflagellate, Luciella gen. nov., and two new species, Luciella masanensis sp. nov. and Luciella atlantis sp. nov., are described. These species commonly occur with other small (<20 lm) heterotrophic and mixotrophic dinoflagellates in estuaries from Florida to Maryland and the southern coast of Korea, suggesting a possible global distribution. An SEM analysis indicates that members of the genus Luciella have the enhanced Kofoidian plate formula of Po, cp, X, 4¢, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…The thecate heterotrophic dinoflagellate Luciella masanensis (NC Lucy, P27; Mason et al 2007), an isolate from the New River Estuary, North Carolina, USA, was obtained from Dr. Patricia Tester at the NOAA Laboratory in Beaufort, North Carolina. Both P. piscicida and L. masanensis were re-isolated at the Virginia Institute of Marine Science (VIMS), and the re-isolated heterotrophic protists were used for our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thecate heterotrophic dinoflagellate Luciella masanensis (NC Lucy, P27; Mason et al 2007), an isolate from the New River Estuary, North Carolina, USA, was obtained from Dr. Patricia Tester at the NOAA Laboratory in Beaufort, North Carolina. Both P. piscicida and L. masanensis were re-isolated at the Virginia Institute of Marine Science (VIMS), and the re-isolated heterotrophic protists were used for our study.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we experimentally investigated the capability and species-specific differences in long-chain n-3 essential fatty acid (LCn-3EFA), sterol, and steroidal ketone production, as well as the bioconversion of dietary sterols for 6 different heterotrophic protists, which included 3 thecate heterotrophic dinoflagellates (Cryptoperidiniopsis brodyi, Pfiesteria piscicida, and Luciella masanensis) isolated in the early and mid-1990s from estuaries on the mid-Atlantic coast of the USA (Steidinger et al 1996, Mason et al 2007), 1 athecate heterotrophic dinoflagellate (Amphidinium longum), 1 herbivorous ciliate (Strombidinopsis sp. ), and 1 bacterivorous ciliate (Uronema sp.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, several new species in this family have been discovered (Jeong et al 2005b, Litaker et al 2005, Mason et al 2007). The present study suggests that species in this family may have a distinct ecological niches and may be differentiated from each other based on their prey species, differential growth and ingestion rates (Lin et al 2004, Jeong et al 2005a, 2007a as well as the differential mortality rate due to predation as shown in the present study.…”
Section: Growth and Ingestion Ratesmentioning
confidence: 99%
“…Since the small heterotrophic dinoflagellate Pfiesteria piscicida (order Peridiniales and family Pfiesteriaceae) was first discovered in the early 1990s (Steidinger et al 1996), several more dinoflagellate species in the family Pfiesteriaceae, such as Cryptoperidiniopsis brodyi, Luciella atlantis, L. masanensis, Pseudopfiesteria shumwayae, and Stoeckeria algicida, have been discovered (Jeong et al 2005b, Litaker et al 2005, Steidinger et al 2006, Mason et al 2007). Both scientists and the public have paid attention to these dinoflagellates because some of the species are harmful to fish , Glasgow et al 2001, shellfish (Springer et al 2002, Shumway et al 2006, and humans (Schmechel & Koltai 2001).…”
Section: Introductionmentioning
confidence: 99%
“…They have also been found to participate in reciprocal predator-prey interactions with mixotrophic dinoflagellates (Jeong et al 1997). Recently several HTD species such as Pfiesteria piscicida, Pseudopfiesteria shumwayae, Stoeckeria algicida, and Luciella masanensis (previously Lucy) have been newly discovered (Steidinger et al 1996, Litaker et al 2005, Jeong et al 2005b, Mason et al 2007). These heterotrophic dinoflagellates are harmful to finfish and shellfish due to their feeding on the blood cells and flesh of fish.…”
Section: Introductionmentioning
confidence: 99%